Treatment with curative intent and survival in men with high‐risk prostate cancer. A population‐based study of 11 380 men with serum PSA level 20–100 ng/mL. (3rd July 2012) - Ladjevardi, Sam; Berglund, Anders; Varenhorst, Eberhard; Bratt, Ola; Widmark, Anders; Sandblom, Gabriel
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? There are two randomized controlled trials showing that radiotherapy can be beneficial for men with locally advanced prostate cancer. The present study confirms the importance of curative treatment for men with high‐risk prostate cancer. Objective To investigate the influence of curative treatment on cause‐specific mortality in men diagnosed with prostate cancer (PCa) with serum prostate‐specific antigen (PSA) levels between 20 and 100 ng/mL. Materials and Methods Patients with PCa (T1–4, N0/N1/NX, M0/MX), PSA 20–100 ng/mL and age ≤75 years were identified in the National Prostate Cancer Register of Sweden. Data on co‐morbidity diagnoses were obtained from the National Patient Register and cause of death from the Cause of Death Register. Following adjustment for age at diagnosis, co‐morbidity burden, Gleason score, T‐category, PSA level and cause‐specific mortality in relation to treatment were estimated using Cox regression analysis. Result A total of 11 380 men were diagnosed with PCa between 1996 and 2008 and fulfilled the inclusion criteria. The cumulative 10‐year PCa‐specific mortality was 36% for patients receiving only palliative treatment and 13% for those treated with curative intent. For the 8462 (74%) patients with PSA levels from 20 to 50 ng/mL at diagnosis, the hazard ratio for death from PCa was 0.23 (95% confidence interval 0.19–0.27) for those treated with curative intent compared with those given palliative treatment after adjusting for age, co‐morbidity, T category, PSA level and Gleason score. The corresponding hazard ratio was 0.22 (95% confidence interval 0.17–0.30) for patients with PSA levels from 51 to 100 ng/mL. Conclusion Treatment with curative intent for men with high‐risk PCa was associated with reduced cause‐specific mortality and should be considered even when serum PSA exceeds 20 ng/mL.